2017
DOI: 10.1080/09537287.2017.1375144
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the factors that influence the acceptance of digital technologies in e-government services in the UAE: a PLS-SEM Approach

Abstract: The digital technologies such as internet play a crucial role in the management of operations of organizations in both public and private sectors. Such technologies support the implementation of effective digital business strategies. By reviewing the extant literature, this paper aims to identify factors that influence the intention to use digital technologies in order to develop a theoretical model which is then tested empirically using the PLS-SEM approach. While many studies have focused solely on the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 47 publications
(24 reference statements)
2
26
0
Order By: Relevance
“…AW in this study is mediated by PU and PEOU to predict intention to use the digital currencies in the UAE. In this regard, similar results were reported by Jasimuddin et al (2017), in that awareness was not a direct significant factor influencing ITU, which is supposed to be prerequisite to usage and benefits (Almuraqab, 2017). This finding contradicts those of Shahzad et al (2018), who reported that AW is a direct significant determinant of citizens' intention to use Bitcoin in China.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…AW in this study is mediated by PU and PEOU to predict intention to use the digital currencies in the UAE. In this regard, similar results were reported by Jasimuddin et al (2017), in that awareness was not a direct significant factor influencing ITU, which is supposed to be prerequisite to usage and benefits (Almuraqab, 2017). This finding contradicts those of Shahzad et al (2018), who reported that AW is a direct significant determinant of citizens' intention to use Bitcoin in China.…”
Section: Discussionsupporting
confidence: 82%
“…A study by Baur et al (2015) on Bitcoin adoption argued for the importance of social influence, and how word-of-mouth enhanced and triggered the adoption of digital currency (Bitcoin) as a fiat currency. This is in line with studies (Almuraqab, 2017;Jasimuddin, Mishra, & Almuraqab, 2017) that have demonstrated the significance of social influence on adoption of technology, so it is hypothesized that H6. Social influence will have a positive influence on UAE citizens' intention to use digital currency.…”
Section: Social Influencesupporting
confidence: 86%
“…Despite, the fact that many researchers have criticized the TAM; for instance, Gillenson and Sherrell (2002) pointed out TAM's failure to account for social influence on the adoption of new technologies, and Chen and Huang (2006) are critical of this model's low explanatory power. This has led to further investigations of the studies that adopted TAM, in which we found that current studies have addressed these criticisms by incorporating other theories, such as DOI (Saadi et al 2017), or considering external factors, such as social influence (Jasimuddin et al 2017). Analysis of the current studies showed that TAM was the most used theory because of its flexibility in incorporating external factors and other theories.…”
Section: Discussionmentioning
confidence: 73%
“…The most common recommendations were related to the use of additional or more relevant factors and variables. For instances, demographic variables (Saxena 2017;Jasimuddin et al 2017;Saadi et al 2017;Almuraqab 2017), cost (Glood et al 2016a;ElSherif et al 2016; Abu-Shanab and Haider 2015) and security (Glood et al 2016a;Glood et al 2016b;Alrowili et al 2015).…”
Section: Recommendations Of Reviewed Studiesmentioning
confidence: 99%
“…It is also important to note majority of the previous studies on e-government adoption have focused on citizens (e.g. Al-Shafi et al, 2009;Carter and Schaupp, 2008;McLeod et al, 2009;Chan et al, 2010;Schaupp et al, 2010;Jasimuddin et al, 2017) rather than employees of the public sector (Gupta et al, 2008;Dasgupta and Gupta, 2011). To fill this gap, the current study aims to identify the factors that impact attitude of 'early adopters' towards adoption of IT/IS and the focus is on public sector employees rather than citizens.…”
Section: Introductionmentioning
confidence: 99%